MODEL MANAJEMEN RISIKO DALAM ADMINISTRASI PERTAHANAN: Kajian Literatur Sistematis Terhadap Ancaman Hibrida Dan Non-Militer - Khairul Muslim; Taufik, Ahmad (PPM Sdirjianbang Akademi Militer, 2025)
Defense administration faces complex challenges from hybrid and non-military threats that undermine national defense effectiveness. This study aims to formulate an adaptive risk management model through a systematic literature review of 35 academic articles, policy reports, and international standards. Data were analyzed using content analysis and thematic coding, adopting the ISO 31000:2018 framework and NATO AJP-3.15 doctrine. The findings highlight five key stages of risk management—identification, analysis, evaluation, mitigation, and monitoring—enriched with whole-of-government and whole-of-society principles. The novelty of this research lies in synthesizing international frameworks with Indonesia’s local context, producing a conceptual model of defense administration that is systematic, participatory, and responsive. These findings imply significant contributions for the Ministry of Defense and the Armed Forces in strengthening national defense resilience against multidimensional threats.